Linguistic consistency in women’s rhetorics - Azahra Hassan Radi Obaid Al-Azzawi, Dr. (lark, 2026)
When examining the use of language among Arabs, we find that Arab taste is based on linguistic consistency in using the phonetic, morphological, and grammatical systems correctly and sequentially. Language is a customary organization that symbolises the activity of society, and this organization includes a number of systems, including the phonetic system, the morphological system, and the grammatical system. This is what can be expressed through linguistic consistency, which is phonetic, morphological, grammatical, or all of them, and these are the most beautiful forms. Through these aspects, we review some of the eloquent women’s sermons that Ibn Tayfour (died 280) AH presented in his book Balaghat al-nisa’, which was written in an early period of the beginnings of writing in the Arab-Islamic heritage. It is considered a pioneering and unprecedented book in this context, as it is rich in material that depicts the languages of women between pre-Islamic times and Islam. through what was narrated about them in poetry and prose.